Comparative Efficacy of Triple Versus Quadruple Therapy for the Eradication of Helicobacter pylori Infection in Asian Adults—A Systematic Review and Meta‐Analysis - Abdur Razzak; Nymur Rahman; Nikkon Sarker; Monira Swapna Nil; Md. Arifur Rahman; Md. Toslim Mahmud (JGH Open, 2025)
ABSTRACT Helicobacter pylori infection remains a major health issue in Asia due to its strong association with gastric ulcers and cancer. Rising antibiotic resistance has reduced the success of standard triple therapy, leading to broader use of bismuth‐based quadruple regimens. However, the relative effectiveness of these regimens in Asian populations remains uncertain. To evaluate which treatment is more effective in Asian populations, this systematic review and meta‐analysis assessed randomized controlled trials comparing these two regimens. A comprehensive search across four major databases (PubMed, Web of Science, The Cochrane Library, and Scopus) up to May 2024 retrieved 16,398 studies. After thorough title and abstract (TIAB) and full‐text screening, nine eligible studies involving 2266 adult patients from six Asian countries were included for this analysis. The analysis showed that quadruple therapy achieved higher eradication rates than triple therapy within all nine studies, with a pooled risk ratio of 1.21 (95% CI: 1.09–1.35; p = 0.0003), indicating a 21% greater likelihood of treatment success. Although adverse effects were somewhat more frequent with quadruple therapy, adherence remained high in most trials. The overall risk of bias was low to moderate. These findings support the use of quadruple therapy as a more effective first‐line option for H. pylori eradication in Asia, especially in regions where clarithromycin resistance is common. Further research should focus on optimizing regimen tolerability and incorporating local antibiotic resistance patterns to guide treatment.